Signs of Reincarnation: Exploring Beliefs, Cases, and Theory by James Matlock - Sudduth, Michael (Journal of Scientific Exploration, 2021)
James Matlock’s Signs of Reincarnation discusses important issues related to the belief in reincarnation. These include the historical and social prominence of this belief in various cultures around the world, especially its place in spiritual and religious communities. Matlock also explores data seemly suggestive of reincarnation and attempts to develop a theory of reincarnation that can account for the data collected by parapsychological investigators and researchers. In this way, Matlock aims to show that belief in reincarnation is defensible as a conclusion drawn from what he calls “signs” of reincarnation. Matlock does a good job mapping out the wide range of beliefs about reincarnation across time and culture. His description of various case studies and their salient features is highly informative. And his effort to develop a theory of reincarnation—what he calls a “processual soul theory”—is a laudable attempt at trying to accommodate the various details of interesting case studies and a core idea of reincarnation in the spiritual traditions of the world. Unfortunately, this is where my praise ends. Like many other books on the topic, Matlock’s book suffers from a variety of serious defects. The cavalcade of poor scholarship, conceptual confusion, and impoverished argumentation is particularly egregious given that Signs is allegedly based on the lecture notes for Matlock’s course on reincarnation pitched at the advanced undergraduate or Masters-level graduate seminar. In what follows, I’ll explain why Matlock’s book is paradigmatic of nearly everything that’s wrong with survival research over the past thirty years.